Midwives’ knowledge, risk perceptions, preventive behaviour and adherence to infection control regarding Covid-19: Cross-sectional study in Indonesia - Rosyidah, Hanifatur; Sutrisminah, Emi; Tamang, Indra Kala (Universitas Aisyiyah Yogyakarta, 2022)
Midwives are at the highest risk of getting COVID-19 in maternity wards. This study aimed to assess factors determining the knowledge, attitude and prevention of midwives towards COVID-19 in Indonesia. A cross-sectional online survey was conducted among 478 midwives spreading through whatsapp from December 2020 to January 2021. The factors knowledge, attitude and practice of midwives were estimated using 11, 7 and 7 questions, respectively. A multivariable logistic regression analysis was used on SPSS version 23 to identify factors related to the knowledge, attitude and prevention practice of midwives on COVID-19. Significance was determined at a p value of < 0.05 and association was described by using odds ratio at 95% CI. Among 478 midwives, 92.3% has a good behaviour to protect them from Covid-19, 78.2% have good attitude and 40.2% have poor knowledge.Â There was no relationship between respondents' socio-demographic characteristics and their knowledge. The availability PPE, disinfectant and IP guidelines significantly influence preventive behaviour of midwives.Training and availability of equipment are recommended to ensure a good knowledge, attitude and practice of midwives.